Proteomic and microscopic approaches in understanding mechanisms of shell-loosening of shrimp (Pandalus borealis) induced by high pressure and protease. (15th August 2019) - Dang, Tem Thi; Jessen, Flemming; Martens, Helle Juel; Gringer, Nina; Olsen, Karsten; Bøknæs, Niels; Orlien, Vibeke
Highlights: Shrimp shell-loosening gap induced by high pressure and enzymes was quantified by microscopy. Protein changes in epidermis and shell were evaluated by 2D gel electrophoresis. Relationship between protein changes and the shell-loosening gap was established. The shell-loosening gap could be predicted from the protein fold change using PLS regression. Degradation and loss of cuticular and epidermal proteins is the mechanism of shell-loosening. Abstract: Shell-loosening is of importance in facilitating shrimp peeling. In this study, enzyme and high pressure (HP) improved the shell-loosening at different degrees, which were observed as gaps by microscopy. The shell-loosening gap induced by an endoprotease with broad specificity (Endocut-03L, 53 μm) was much higher than that induced by HP at 100 MPa (HP100, 12 μm), followed by an endoprotease with high specificity (Tail21, 8 μm), and HP at 600 MPa (HP600, 5 μm). The degree of shell-loosening was found to be correlated to the extent of protein changes that were obtained by 2D gel electrophoresis. Shell-loosening due to HP100 and Endocut-03L was mainly caused by physical and enzymatic degradation of high molecular-weight proteins in shell and epidermis and subsequent loss of degradation products, disrupting the structure of muscle-shell connection. However, HP100 was less effective than Endocut-03L due to its stabilizing effect on the shell collagen, lowering its shell-loosening effect.